Moxibustion with Chinese herbal has good effect on allergic rhinitis - Min, Cunyun (Int J Clin Exp Med, 2015)
Allergic rhinitis (AR) is a chronic inflammatory disease of rhino-ocular mucosa, affecting up to 40% of population worldwide. Chinese herbal medicines and Acupuncture, adopted thousands of years in China, has good effect on allergic rhinitis. This study evaluates the effects of Moxibustion with Chinese herbal in treating patients with allergic rhinitis over a 1-year follow-up. A randomized controlled trial was conducted in a sample of 355 participants recruited from Guangdong general hospital of China. After baseline measurements, participants were randomly assigned to treatment-group or control group. Treatment group received Moxibustion with Chinese herbal. Control group received Loratadine. The main outcomes, including symptom severity and quality of life were measured using the Allergic Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ). Both moxibustion with Chinese herbal and Loratadine improve nose symptoms such as stuffy/blocked, sneezing, runny nose, itchy nose, sore nose and post-nasal drip in patients with AR. Symptoms fatigue, loss of taste, afraid of cold/wind and cold limb were improved significantly in moxibustion with Chinese herbal group. The mean quality of life scores decreased in both groups after treatment. Compare to control group, moxibustion with Chinese herbal is more effective than Loratadine in improving the quality of life in patients with AR. The results show moxibustion with Chinese herbal was effective to reduce symptoms and enhance quality of life in patients with allergic rhinitis. It is a simple, convenient and economic therapy for patients with AR. Further controlled trials of its effects in patients with allergic rhinitis are recommended.